Synthesis of TiO2/FeCo magnetic nanoparticles as a nano-coagulant for removal of fluoride in semiconductor wastewater - Yap, Brendan Ee Herng (Nanyang Technological University, 2023)
The project aim is to study the pairing of TiO2 nanotubes and FeCo nanoparticles as a novel treatment method to remove fluoride content from semiconductor wastewater. The research is split into two papers – Si Yuan’s FYP report and this report. This report covers the synthesis of TiO2 nanotubes using the sonicated hydrothermal process, and the synthesis of FeCo nanoparticles using coprecipitation. TiO2 nanotubes synthesised via the sonication hydrothermal method showed a significant increase in length of nanotube due to effects of sonication. However, energy dispersive X-ray (EDX) and X-ray diffraction (XRD) showed the presence of Na in sample B1 and is assumed to have caused a reduction in length of nanotube. FeCo nanoparticles were synthesised using the coprecipitation method with ferric chloride and cobalt nitrate hexahydrate as precursors in the presence of ethanol glycol as dispersant. A total of two batches were synthesised with one having higher Fe concentrations (120723) and vice versa. It was observed that the batch (090723) with lower Fe concentrations displayed no magnetic properties. FESEM results revealed successful synthesis of the nanoparticles coated with the nanotubes, EDX and XRD results revealed that the nanoparticles were of low purity due to presence of impurities that were not properly removed during synthesis. The synthesis method needs to be reviewed again to remove/reduce the impurities present.